Order and disorder in intermediate filament proteins. Issue 19 (29th July 2015) - Kornreich, Micha; Avinery, Ram; Malka-Gibor, Eti; Laser-Azogui, Adi; Beck, Roy
Abstract : Intermediate filaments (IFs), important components of the cytoskeleton, provide a versatile, tunable network of self‐assembled proteins. IF proteins contain three distinct domains: an α‐helical structured rod domain, flanked by intrinsically disordered head and tail domains. Recent studies demonstrated the functional importance of the disordered domains, which differ in length and amino‐acid sequence among the 70 different human IF genes. Here, we investigate the biophysical properties of the disordered domains, and review recent findings on the interactions between them. Our analysis highlights key components governing IF functional roles in the cytoskeleton, where the intrinsically disordered domains dictate protein–protein interactions, supramolecular assembly, and macro‐scale order.